Nowe aspekty prawne samorządu załogi przedsiębiorstwa państwowego - Rabska, Teresa (Wydział Prawa i Administracji UAM, 1982)
A new shape of self-management in State-run enterprises came up for a heated discussion what can indicate the key importance of this question in the shifting policies of management of the national economy. Two bills: the Act of Workers' Self Management in the State Enterprises and the State Enterprises Act were passed in the Seym at the same time. In spite of their formal distinction, these statutes are closely interrelated and in principle they can be neither interpreted nor applied separately. Although of a wide scope, the Self Management Act does not govern all the enterprises and in some instances the provisions of the Act are applied to a various extent. It is mostly a case of the right to appoint a manager of the enterprise. The self management is to be treated as a compulsory institution within a meaning of the law, the obligation to constitute the self management is consequent upon the legal regulation. It has to be a separate organization within a structure of the enterprise, not linked with trade unions and with other social or political organizations. A personnel of the enterprise'is the subject of self management excercising its power (competence) directly on. the staff meetings or indirectly via the worker's council, the body elected by the personnel. The bodies of self-management are recognized as organs of the enterprise along with a director, the one-man professional organ, and they act independently of administrative bodies of the State. The new legislation grants a vast competence to the bodies of the self management to decide of the essential problems of the enterprise (including a resolution of plans). The definite scope of the competence will however remain to become a subject of further regulation of the main spheres of economic activity (planning, financing, taxation and pricing). Operation of the self-management is commited to the care of the Seym. Disputes under functioning of the self-management will in the last resort be resolved in court.
New Legal Aspects of Worker's Self-Management in a State- -Run Enterprise